THE ANTI-INFLAMMATORY AND ANTI-NOCICEPTIVE ACTIVITIES OF PATRINIA VILLOSA AND ITS MECHANISM ON THE PROINFLAMMATORY CYTOKINES OF RATS WITH PELVIC INFLAMMATION - Zheng, Yan; Jin, Yue; Zhu, Hai-Bin; Xu, Shao-Ting; Xia, Ya-Xian; Huang, Yue (African Journal of Traditional, Complementary and Alternative Medicines, 2012)
This study explores the anti-inflammatory and anti-nociceptive activities of Patrinia villosa, a Chinese medicinal plant, and to explore its effects on the proinflammatory cytokines of the rats with pelvic inflammation model. The animals were randomly divided into Patrinia villosa group (PV group), dexamethasone group (DEX group), and model-control group (CON group) to perform an ear edema test, a carrageenin-induced paw edema test, a cotton pellet-induced granuloma formation test, and an acetic acid-induced writhing test. The model rats with pelvic inflammation were established, and the serum levels of interleukin-6 (IL-6), interleukin-8 (IL-8) and tumor necrosis factor-alpha (TNF-α) in each group was detected with the Enzyme-Linked ImmunoSorbent Assay (ELISA). The results of the ear edema test, carrageenin-induced paw edema test, cotton pellet-induced granuloma formation test, and acetic acid-induced writhing test all showed that Patrinia villosa had strong anti-inflammatory and anti-nociceptive effects. In the experiment using model rats with pelvic inflammation, we found that the serum levels of IL-6, IL-8 and TNF-α in PV and DEX group were all significantly lower than those of the CON group, and the serum levels of IL-6 and IL-8 in PV group were significantly lower than those of the DEX group. Patrinia villosa, with its strong anti-inflammatory and anti-nociceptive activities, can be used to treat pelvic inflammation and to relieve the associated pain.